Cyclic alternating pattern in sleep and its relationship to creativity - Drago, Valeria <1977> (Alma Mater Studiorum - Università di Bologna, 2011)
Background/Objectives: Sleep has been shown to enhance creativity, but the reason for this enhancement is not entirely known. There are several different physiological states associated with sleep. In addition to rapid (REM) and non-rapid eye movement (NREM) sleep, NREM sleep can be broken down into Stages (1-4) that are characterized by the degree of EEG slow wave activity. In addition, during NREM sleep there are transient but cyclic alternating patterns (CAP) of EEG activity and these CAPs can also be divided into three subtypes (A1-A3) according to speed of the EEG waves. Differences in CAP ratios have been previously linked to cognitive performances. The purpose of this study was to learn the relationship CAP activity during sleep and creativity. Methods: The participants were 8 healthy young adults (4 women), who underwent 3 consecutive nights of polysomnographic recording and took the Abbreviated Torrance Test for Adults (ATTA) on the 2 and 3rd mornings after the recordings. Results: There were positive correlations between Stage 1 of NREM sleep and some measures of creativity such as fluency (R= .797; p=.029) and flexibility ( R=.43; p=.002), between Stage 4 of Non-REM sleep and originality (R= .779; p=.034) and a global measure of figural creativity (R= .758; p=.040). There was also a negative correlation between REM sleep and originality (R= -.827; p= .042) . During NREM sleep the CAP rate, which in young people is primarily the A1 subtype, also correlated with originality (R= .765; p =.038). Conclusions: NREM sleep is associated with low levels of cortical arousal and low cortical arousal may enhance the ability of people to access to the remote associations that are critical for creative innovations. In addition, A1 CAP activity reflects frontal activity and the frontal lobes are important for divergent thinking, also a critical aspect of creativity.